The Poverty-Related Stress Scale: Development and Validation of a Multidimensional Measure Assessing Poverty-Related Stressors - Allen, Brianna; Klibert, Jeffrey; van Zyl, Llewellyn E. (Depression and Anxiety, 2023)
Background. Poverty-related stress plays a pivotal role in mediating the impact of poverty on behavioral health outcomes. However, existing research on adult poverty-related stress suffers from limited scope and inadequate measurement approaches. To address these shortcomings, our study undertakes a comprehensive investigation to develop and validate a multidimensional Poverty-Related Stress Scale (PRSS). Methods. A multistudy research design was employed to develop and validate the PRSS. Study 1 (N=206) established a multidimensional framework for poverty-related stress by exploring the factor structure and internal consistency of our measure. Study 2 (N=400) evaluated nuanced psychometric properties, including factorial validity, internal consistency, and temporal invariance, using confirmatory factor analyses (CFA) and modern exploratory structural equation models (ESEM). Lastly, Study 3 (N=470/219) examined the criterion validity of our scale by investigating its concurrent and predictive relationships with depression, anxiety, and flourishing. Results. The findings consistently supported a hierarchal ESEM model for overall poverty-related stress, reflecting the dynamic interaction among three stressors: noise disturbance, housing dysfunction, and financial distress. This model exhibited temporal invariance, with different studies reliably measuring distinct components of poverty-related stress. Concurrent validity was demonstrated by significant associations between overall poverty-related stress and theoretically relevant constructs, such as depression, anxiety, and flourishing, at different time points. Additionally, predictive validity was established, showing poverty-related stress measured at time 1 accounted for variations in depression, anxiety, and flourishing at time 2. The results provide robust evidence for the validity and reliability of the PRSS as a tool for measuring poverty-related stress and its underlying factors. Conclusions. Our findings offer compelling preliminary support for the utility of our measure. Further research and potential clinical applications are discussed to deepen the understanding of poverty-related stress and its implications for behavioral health outcomes.